2004
DOI: 10.1074/jbc.m312079200
|View full text |Cite
|
Sign up to set email alerts
|

A Krüppel-like factor KLF15 Contributes Fasting-induced Transcriptional Activation of Mitochondrial Acetyl-CoA Synthetase Gene AceCS2

Abstract: Acetyl-CoA synthetase 2 (AceCS2) produces acetylCoA for oxidation through the citric acid cycle in the mitochondrial matrix. AceCS2 is highly expressed in the skeletal muscle and is robustly induced by fasting. Quantification of AceCS2 transcripts both in C2C12 and human myotubes indicated that fasting-induced AceCS2 gene expression appears to be independent on insulin action. Characterization of 5 -flanking region of the mouse AceCS2 gene demonstrates that Krü ppel-like factor 15 (KLF15) plays a key role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 29 publications
1
68
0
Order By: Relevance
“…KLF15 function may involve the regulation of other important transcriptional pathways and physiologic processes in the myocardium. We have previously reported that KLF15 regulates GLUT4 expression in adipose (24) and others have reported that KLF15 regulates mitochondrial acetyl-CoA synthase expression in skeletal muscle (42) and PEPCK expression in hepatocytes (43). In our initial evaluation we did not observe any significant difference in GLUT4 mRNA between KLF15 (ϩ/ϩ) vs. (Ϫ/Ϫ) hearts (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…KLF15 function may involve the regulation of other important transcriptional pathways and physiologic processes in the myocardium. We have previously reported that KLF15 regulates GLUT4 expression in adipose (24) and others have reported that KLF15 regulates mitochondrial acetyl-CoA synthase expression in skeletal muscle (42) and PEPCK expression in hepatocytes (43). In our initial evaluation we did not observe any significant difference in GLUT4 mRNA between KLF15 (ϩ/ϩ) vs. (Ϫ/Ϫ) hearts (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…Although a number of KLFs have been identified as expressed in developing or mature skeletal muscle (KLF6 [95], KLF13 [47], KLF15 [40]), there are very few reports describing their regulation and potential roles in this tissue (Table 1) [40,96]. Our group has demonstrated that KLF15 is robustly expressed in skeletal muscle where it regulates expression of the glucose transporter GLUT4.…”
Section: Klfs In Skeletal Musclementioning
confidence: 86%
“…Recently, we have reported that KLF15(−/−) mice have severe fasting hypoglycemia which is caused by a defect in the ability of critical amino acids to enter the gluconeogenetic pathway in the liver [33] though the significance of this metabolic block in the heart or skeletal muscle has not been fully determined. KLF15 has also been shown to regulate the fasting-induced transcriptional activation of mitochondrial acetyl-CoA sythetase-2 in skeletal muscle [96]. Indeed, a deeper understanding of the expression, regulation and functional significance of KLFs in skeletal muscle has important implications for understanding the molecular pathways perturbed in diseases such as diabetes and metabolic syndrome, congestive heart failure, and peripheral arterial insufficiency [2][3][4].…”
Section: Klfs In Skeletal Musclementioning
confidence: 99%
“…Fast Activation of Acetate to Esters-In vivo NMR spectra of acetate metabolism were recorded in mouse heart, liver, and skeletal muscle supplied with hyperpolarized [1][2][3][4][5][6][7][8][9][10][11][12][13] C]acetate. Hyperpolarized in vivo NMR provides sufficient sensitivity to detect conversion of the marker to different molecular species.…”
Section: Resultsmentioning
confidence: 99%
“…by a number of enzymes in mammals including pyruvate dehydrogenase, ␤-ketothiolase, and ATP citrate-lyase (1). A less well-explored metabolic pathway forming acetyl-CoA in mammals is the acetyl-CoA synthetase (AceCS)-catalyzed catabolism of acetate ( Fig.…”
mentioning
confidence: 99%